Hoarseness of voice in the pediatric age group: Our experiences at an Indian teaching hospital - Swain, Santosh Kumar; Behera, Ishwar Chandra; Sahoo, Loknath (Indian Journal of Child Health, 2019)
Background: Hoarseness of the voice or dysphonia is a commonly encountered vocal symptom among children. The etiological profiles of dysphonia among children are variable, and laryngoscopic examination is required for identification of the lesions. Objective: The objective of the study was to study the etiology, clinical presentations, and diagnosis of the hoarseness of voice among children. Materials and Methods: The children aged from 3 to 16 years presenting with dysphonia/hoarseness, were included in this study from October 2015 to September 2018. All the 132 children presented with hoarseness of voice were subjected to video laryngoscopy for voice assessment. Results: The majority of this study was male children (59.09%). Vocal fold nodules (36.36%) were the major cause for dysphonia. Other attributing causes include vocal fold polyp, vocal fold cyst, laryngopharyngeal reflux, hemorrhagic vocal fold polyp, laryngeal papilloma, vocal fold sulcus, and vocal fold paralysis. Voice abuse was an important cause for dysphonia and history of vocal abuse was reported among 61 children (46.21%). The duration of hoarseness ranged from 1 month to 2 years with a mean duration of 3.63±2.31 months. The larynx was examined by laryngeal mirror alone in 23 children (17.42%), fiber-optic laryngoscopy in 88 children (66.66%), and direct laryngoscopy under general anesthesia in 21 cases (15.90%). Voice therapy was done in all children along with vocal hygiene care and micro-laryngeal surgery in 64 cases. Conclusion: Pediatric dysphonia is a common cause for referral to pediatric otolaryngologists and management sometimes variable. Flexible nasopharyngolaryngoscopy is suitable for making an accurate diagnosis.